Multi-wavelength erbium-doped fiber laser using four-wave mixing effect in doped fiber - N. S. Shahabuddin, N. S. Shahabuddin; Z. Yusoff, Z. Yusoff; H. Ahmad, H. Ahmad; S. W. Harun, and S. W. Harun (2011)
We demonstrate a multi-wavelength erbium-doped fiber laser (EDFL) using erbium gain and four-wave mixing (FWM) effect in a piece of erbium-doped fiber (EDF) with high erbium ion concentration. The EDF has a pump absorption rate of 24.6 dB/m at 979 nm and is bi-directionally pumped by 980-nm laser diodes. FWM effect redistributes the energy of different oscillating lines and causes multi-wavelength operation. The laser generates more than 22 lines of optical comb with a line spacing of approximately 0.10 nm at the 1569-nm region using only 1.5-m-long EDF.